The costs of crime to the society in Malaysia - Ishak, Suryati (Zes Rokman Resources, 2016)
Crime has many effects on the daily lives of citizens; it can affect everyone, not just victims. The consequences of criminal activities are the costs incurred, including direct costs (immediate impacts) and indirect costs (long-term effects). This paper provides a preliminary estimation of the monetary costs of crime in Malaysia. For the purpose of this study, only the immediate impact of monetary value was calculated; for example, indirect costs were not included in the cost estimation. A self-administered survey questionnaire or closed ended question was carried out to gather the information on costs of crime in Malaysia. It was found that majority of the respondents were involved in property crime compared to violent crime. The highest number of respondents involved in this crime was from snatch theft. The direct costs involved from this crime can be divided in three which were damage or loss, medical costs and insurance claimed form the crime involved. This paper discusses only on the loss of crime based on the property crime involved.